Psychosocial Interventions for Bipolar Disorder and Coping Style Modification: Similar Clinical Outcomes, Similar Mechanisms?. (August 2013) - Parikh, Sagar V; Hawke, Lisa D; Zaretsky, Ari; Beaulieu, Serge; Patelis-Siotis, Irene; MacQueen, Glenda; Young, L Trevor; Yatham, Lakshmi; Velyvis, Vytas; Bélanger, Claude; Poirier, Nancy; Enright, Jean; et al.
Objective: To investigate changes in the use of coping styles in response to early symptoms of mania in cognitive-behavioural therapy (CBT), compared with psychoeducation, for bipolar disorder. Method: Data were drawn from a randomized controlled trial comparing CBT and psychoeducation. A subsample of 119 participants completed the Coping Inventory for the Prodromes of Mania and symptom assessments before treatment and 72 weeks later. Results: Both CBT and psychoeducation were associated with similar improvements in symptom burden. Both treatments also produced equivalent improvements in stimulation reduction and problem-directed coping styles, but no statistically significant change on the endorsement of help-seeking behaviours. A treatment interaction showed that a reduction in denial and blame was present only in the CBT treatment condition. Conclusions: CBT and psychoeducation have similar impacts on coping styles for the prodromes of mania. The exception to this is denial and blame, which is positively impacted only by CBT but which does not translate into improved outcome. Given the similar change in coping styles and mood burden, teaching patients about how to cope in adaptive ways with the symptoms of mania may be a shared mechanism of change for CBT and psychoeducation.